1982
DOI: 10.1055/s-2008-1055063
|View full text |Cite
|
Sign up to set email alerts
|

Langzeitergebnisse nach Goniotomie

Abstract: Between 1961 and 1968 140 goniotomies were performed at the Department of Ophthalmology, University of Hamburg. The condition of 72 eyes was evaluated and 41 eyes were re-examined. The average intraocular pressure was 33 mmHg preoperativly and only 20 mmHg 13 to 20 years after the goniotomy procedure. Patients from this group with buphthalmus had an even lower pressure of only 17.6 mmHg. Pressure regulation was achieved in 85% of the evaluated eyes by one or more operations, in conjunction with drug therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…A number of articles have investigated the efficacy of trabeculotomy [1,10,11,20,21,24,25,30,33,36,40,44,46] and modifications of trabeculotomy [5,6,14,17,18,26,32,35,41] in congenital glaucoma, as well as goniotomy [15,16,19,29,31,37,48] and modifications of goniotomy [28,53]. In our own retrospective comparative study we found a comparable efficacy of trabeculotomy and goniotomy [39].…”
Section: Introductionsupporting
confidence: 52%
“…A number of articles have investigated the efficacy of trabeculotomy [1,10,11,20,21,24,25,30,33,36,40,44,46] and modifications of trabeculotomy [5,6,14,17,18,26,32,35,41] in congenital glaucoma, as well as goniotomy [15,16,19,29,31,37,48] and modifications of goniotomy [28,53]. In our own retrospective comparative study we found a comparable efficacy of trabeculotomy and goniotomy [39].…”
Section: Introductionsupporting
confidence: 52%
“…Goniotomy and trabeculotomy techniques that do not remove the trabecular meshwork have historically been seen as less successful in adult glaucomas as anterior and posterior trabecular meshwork lips may reapproximate and occlude collector channel intakes. This is different from surgery in children where the elastic scleral spur retracts posteriorly after the incision separating the TM lips [24,25]. It was soon recognized that a TM stripping technique is more successful, but a modified anterior chamber access was necessary to do so without the use of intracameral viscoelastic [26].…”
Section: Discussionmentioning
confidence: 99%
“…Goniotomy and trabeculotomy techniques that do not remove the trabecular meshwork have historically been seen as less successful in adult glaucomas as anterior and posterior trabecular meshwork lips may reapproximate and occlude collector channel intakes. This is different from surgery in children where the elastic scleral spur retracts posteriorly after the incision separating the TM lips (Luntz & Livingston, 1977;Draeger, Wirt & von Domarus, 1982) . It was soon recognized that a TM stripping technique is more successful, but a modified anterior chamber access was necessary to do so without the use of intracameral viscoelastic (Quintana, 1985) .…”
Section: Discussionmentioning
confidence: 93%